2016
DOI: 10.1371/journal.pone.0168862
|View full text |Cite
|
Sign up to set email alerts
|

About the Sterilization of Chitosan Hydrogel Nanoparticles

Abstract: In the last years, nanostructured biomaterials have raised a great interest as platforms for delivery of drugs, genes, imaging agents and for tissue engineering applications. In particular, hydrogel nanoparticles (HNP) associate the distinctive features of hydrogels (high water uptake capacity, biocompatibility) with the advantages of being possible to tailor its physicochemical properties at nano-scale to increase solubility, immunocompatibility and cellular uptake. In order to be safe, HNP for biomedical app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 45 publications
3
21
1
1
Order By: Relevance
“…High and negative zeta potential values are an indication of stable preparations and prevent aggregation phenomena [47). PDI parameter approved homogeneity of our suspension that values of less than 0.3 corresponded to a single, rather than a sharp peak, in the DLS profile [48]. In the case of our samples, a single and homogeneous population was detected, except for bare niosome.…”
Section: Resultsmentioning
confidence: 60%
“…High and negative zeta potential values are an indication of stable preparations and prevent aggregation phenomena [47). PDI parameter approved homogeneity of our suspension that values of less than 0.3 corresponded to a single, rather than a sharp peak, in the DLS profile [48]. In the case of our samples, a single and homogeneous population was detected, except for bare niosome.…”
Section: Resultsmentioning
confidence: 60%
“…Thus, it is necessary to find better sterilization conditions that do not modify the physicochemical properties of the NP. Even the sterilization efficacy of low doses of gamma irradiation (8 and 13 kGy) has been demonstrated [20] in the presence of some protective sugars such as glucose and mannitol at 5% in chitosan hydrogel-NP. Usually, the presence of cryoprotective agents is in considerable quantities in the final batches of NP, so it is reasonable to consider an additional effect of that excipient.…”
Section: Introductionmentioning
confidence: 99%
“…The steam sterilization method is easy to use, low‐cost, nontoxic, and environmentally friendly (Shamekhi et al, ). However, the temperature applied during steam sterilization frequently has adverse effects on the physicochemical, mechanical, and biological properties of the hydrogels (Galante et al, ; Yu‐Min, Ya‐Hong, Xiao‐Hua, Fei, & Xiao‐Song, ; Zang et al, ). Ji and Shi () observed that steam sterilization impacted the physicochemical and mechanical properties such as porosity, swelling, compressive modulus, and biocompatibility of freeze‐dried chitosan scaffolds.…”
Section: Introductionmentioning
confidence: 99%